2008
DOI: 10.1111/j.1600-0668.2008.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled formaldehyde on learning and memory of mice

Abstract: This study indicates that inhaled formaldehyde starts to negatively affect learning and memory at a middle concentration of formaldehyde without interference of other indoor air pollutants. Oxidative damage, and the alteration of NMDA receptor expression, which were induced by formaldehyde inhalation, may be the possible mechanism for gaseous formaldehyde-induced neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 26 publications
2
92
0
Order By: Relevance
“…Experiments on animals have demonstrated that low-level exposure to FA by inhalation has an impact on oxidant stress in a tissue-specific manner [2]. In addition, inhalation of FA has been shown to inhibit learning and memory performance in mice [3].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on animals have demonstrated that low-level exposure to FA by inhalation has an impact on oxidant stress in a tissue-specific manner [2]. In addition, inhalation of FA has been shown to inhibit learning and memory performance in mice [3].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Inhaled FA has also been shown to cause behavioral and memory disorders in rats and has been defined as probably cytotoxic. [14][15][16] Long-term exposure to FA from 14 to 30 years may cause irreversible neurotoxicity and was suggested to be related to astrocytoma in the brain. [17] Because neurons have an elevated metabolic rate and high content of oxidizable substrates, neural tissues are highly sensitive to free radical attacks.…”
mentioning
confidence: 99%
“…Many studies have discussed the toxic effects of FA on the central nervous system [62] [64] [65]. Long-term exposure to FA can lead to irreversible neuro-…”
Section: Experimental Studymentioning
confidence: 99%